Regeneração natural em fragmento florestal urbano (Uberlândia,MG) - Salles, Jania Cabrelli (2004)
This study was carried out in semideciduous seasonal forest fragment, subject to different types of anthropogenic disturbance, located in the urban area of Uberlândia, MG. The objective was to know the floristic composition and the structure of the regeneration layer (ER), and to compare with the structure of the adult plant community, in order to obtain instantaneous information on the environmental dynamics. Using this basic surveys is possible to estimate the quantitative and qualitative changes in the vegetation and canopy species composition in the future. In 30 plots of 10m X 10m, the individuais with height equal or greater than one meter that were not included in the inventory of the tree layer (EA), were measured for their height and diameter at soil levei. In the ER, were surveyed 1.268 individuais, included in 63 species of 32 families, with estimated density of 4.226 ind./ha. The Shannon Index of Diversity was 3,105 nats./ind., where 50,62% of the individuais were represented for only five species. The density of individuais in the regeneration layer was higher than within the adult community, due to hígher rates of mortality accumulated in this phase of life. The smallest Index of Diversity of ER in relation to EA, is due to the high density presented by a small number of species in this layer. Piptocarpha macropoda, the most important specie of the ER, is a pioneer tree, that presents larger density and individuais with larger size in disturbance conditions, as gaps or edges, confirming its successional position. The canopy of the seasonal forest of the Parque do Sabiá is composed of trees, probably possessed decades old and gap formation, natural or anthropogenics, stimulates the establishment of pioneer species and the growth of young groups. In general, the important species of ER suggest that the community is suffering changes in its floristic composition, in a succession process, characterized by presence of high number of young individuais, of species belonging to the initial stages of succession.